FORMULASI MEDIA ALTERNATIF DARI KULIT SINGKONG, PISANG, DAN WHEY UNTUK Lactobacillus bulgaricus - Moch. Wachid; Yasmin Nurinbaity; Noor Harini; Elfi Anis Saati; Vritta Amroini Wahyudi (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2021)
De Man Rogose and Sharpe (MRS) growth medium is a specific growth medium for lactic acid bacteria (LAB) but has a relatively expensive price. This can be overcome by making alternative media from waste materials. This study used Lactobacilus bulgaricus to represent LAB analyzed for growth. The research aims to formulate alternative media from the waste of cassava peels, banana peels, and tofu whey; determine the best formulation based on the growth parameters of L. bulgaricus; apply the L. bulgaricus in soygurt making and analyze the quality of the resulting yogurt. The results showed the composition of cassava peel: banana peel (75:25 w/w) with the addition of urea 1.5% as the best formu-lation. This formula yields a total LAB of 8.6x106 CFU/mL. The total LAB in the alternative medium was higher than that in MRS control at 1.7x106 CFU/mL. Soygurt produced from LAB as a result of growth from the best media [cassava peel+banana peel (75:25) with the addition of 1.5% urea] resulted in a fat content of 0.9%, total titrated acid 0.6%, protein 8.1 %, pH 4.7, viscosity 14.2 dPas, total dissolved solids 9.7°Brix, brightness (L) 64.3, and yellow-blue (b +) 10.1. These fat content, total titrated acid, and protein are in accordance with SNI for yogurt 2981: 2009.